2022
DOI: 10.3389/fgene.2022.899923
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms and AR: A Systematic Review and Meta-Analyses

Abstract: Background: Allergic rhinitis (AR) is an especially common disorder associated with both environmental and genetic factors, and a lot of researchers have attempted to find polymorphisms which predisposed to the disease. We conducted a meta-analysis of the most frequently researched polymorphisms to find those genes which may be susceptible to AR and then may be of value in diagnosis.Methods: Pubmed and China National Knowledge Infrastructure (CNKI) databases were searched to screen out eligible studies focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Interestingly, for rs20541, we found that this polymorphism increases the risk of BL-induced hypersensitivity. Like other studies, this polymorphism demonstrated promising genetic effect to various allergic diseases including asthma, 72 allergic rhinitis, 68 atopic dermatitis, and even with alternation of total serum IgE levels. 73 According to dbSNP, this risk allele A accounts for 0.21 of total allele frequency in global population (from 367 982 sample size).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Interestingly, for rs20541, we found that this polymorphism increases the risk of BL-induced hypersensitivity. Like other studies, this polymorphism demonstrated promising genetic effect to various allergic diseases including asthma, 72 allergic rhinitis, 68 atopic dermatitis, and even with alternation of total serum IgE levels. 73 According to dbSNP, this risk allele A accounts for 0.21 of total allele frequency in global population (from 367 982 sample size).…”
Section: Discussionsupporting
confidence: 53%
“…Since IL4R and IL13 play major roles in IgE-mediated activation for allergy, they have been studied widely in different populations since 2004 and have become a promising therapeutic target for allergic reactions in recent years. 67 In particular, rs1801275 polymorphism has been reported as a risk factor for allergic rhinitis 68 and cancer susceptibility, 69 where some other evidence found controversial results. 70 , 71 In this study, we revealed a protective effect of rs1801275 polymorphism in decreasing the risk of BL-induced hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%